Manganese mineralization constrained by redox conditions in the Cryogenian Nanhua Basin, South China and its implications for nitrogen and carbon cycling - Wang, Ping; Wang, Jian; Du, Yuansheng; Yu, Wenchao; Zhou, Qi; Tian, Li; Yuan, Liangjun; Pan, Wen; Wei, Wei; Qin, Yongjun; Ma, Zhixin (Frontiers in Marine Science, 2024)
The Nanhua Basin of South China recorded complete Cryogenian stratigraphic sequence from the Sturtian Glaciation (~717–660 Ma) to the Marinoan Glaciation (~654–635 Ma). The interglacial Datangpo Fm in the Nanhua Basin is divided into two members, and the first member consists of the Mn-carbonate unit and the overlying black shale unit, containing a series of large and superlarge manganese deposits. The metallogenic process of manganese deposits is not clear, and the Mn-carbonates formed through the precursor of Mn-oxide/oxyhydroxide reduction or directly precipitated from an anoxic water column. Moreover, the redox conditions in the deep Nanhua Basin during the precipitation of manganese deposits are also controversial. In this study, the high-resolution nitrogen contents (TN), isotope compositions, carbon isotope compositions of organic and inorganic matter from the first member of the Datangpo Fm are analyzed. The δ15N values of the Mn-carbonate unit (+1.53‰ to +5.26‰, mean +3.36‰) are higher than those of the overlying black shale unit (−3.74‰ to +3.54‰, mean +0.89‰). The Mn contents show a negative relationship with TN but a positive relationship with δ15N in the Mn-carbonate unit, implying that the formation of Mn-carbonates is related to redox variations. The relatively higher δ15N values in the Mn-carbonate unit indicated oxic conditions, and NH4+can be released and partially oxidized during the mineralization of organic matter, resulting in the residual 15N-enriched NH4+ being transferred into clay minerals. Meanwhile, the lower δ15N values in the black shale unit indicated anoxic conditions, which recorded primary N isotope signals. The Mn-carbonate unit is characterized by negative δ13Ccarb values (−11.17‰ to −5.22‰, mean −8.30‰), which show a positive relationship with δ13Corg, but a negative relationship with Mn contents, implying that the negative δ13Ccarb excursions were related to the organic matter degradation during Mn-carbonate formation. The findings of this study indicated that the metallogenesis of manganese deposits in the Cryogenian Nanhua Basin was constrained mainly by the oxic interval in the deep basin. The nitrogen and carbon cycling process can provide new insights into geochemical cycling after the Sturtian Glaciation.